2004
DOI: 10.1038/oby.2004.249
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Obesity Candidate Genes On Porcine Fat Deposition Quantitative Trait Loci Regions

Abstract: 2004;12:1981-1994. Objectives: To investigate possible obesity candidate genes in regions of porcine quantitative trait loci (QTL) for fat deposition and obesity-related phenotypes. Research Methods and Procedures: Chromosome mapping and QTL analyses of obesity candidate genes were performed using DNA panels from a reference pig family. Statistical association analyses of these genes were performed for fat deposition phenotypes in several other commercial pig populations. Results: Eight candidate genes were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…Kim et al (2004) found single polymorphism in the third exon of porcine GHRL gene, which was correlated with a several porcine traits, such as marbling, backfat thickness and weights of loin and ham. Jin et al (2010) investigated several polymorphisms in caprine ghrelin gene and they confirmed association between mutation in second intron (G147A) and growth traits such as: circumference of chest and cannon, and also trunk index (P<0.05 and P<0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al (2004) found single polymorphism in the third exon of porcine GHRL gene, which was correlated with a several porcine traits, such as marbling, backfat thickness and weights of loin and ham. Jin et al (2010) investigated several polymorphisms in caprine ghrelin gene and they confirmed association between mutation in second intron (G147A) and growth traits such as: circumference of chest and cannon, and also trunk index (P<0.05 and P<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In the pig, single polymorphism in third exon has been found so far and according to the authors this mutation is associated with several economically important traits (Kim et al, 2004). The aim of our study was to identify new polymorphisms in the porcine GHRL gene -in exons and in the regulatory regions (promoter region, 5' and 3' untranslated regions).…”
Section: Introductionmentioning
confidence: 99%
“…Two biological candidate genes (ESR and PRLR ) have shown significant association with litter size (Short et al, 1997;Tomas et al, 2006). An MC4R mutation has shown a significant reduction in feed intake with less fat deposition (Kim et al, 2000a;Kim et al, 2004). Additional important genes, PRKAG3 and CAST, have been shown to be associated with changes in pH and tenderness (Ernst et al, 1998;Ciobanu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies on the swine genome have revealed that it is more highly similar to humans than rodents (Wernersson et al, 2005;Hart et al, 2007). We have found that genes involved in obesity-related phenotypes in humans, such as the melanocortin-4 receptor (MC4R) and high-mobility group AT-hook 1 (HMGA1) genes, were associated with fatness traits in pigs (Kim et al, 2000;Kim et al, 2004). Most recently, transcription factor-7-like 2 (TCF7L2) and fat mass and obesityassociated (FTO) genes implicated in T2D in different human cohort studies have been found to be associated with fat and growth rate traits in pigs (Fontanesi et al, 2008;Du et al, 2009;Fan et al, 2009).…”
Section: Introductionmentioning
confidence: 91%